Effect of Myofascial Release as an Adjunct with Conventional Therapy on Range Of Motion and Pain in Post Traumatic Knee Stiffness: Life Sciences-Physiotherapy for better pain management - Gayatri Sunil Landge; Dr. Amrutkuvar Rayjade (International Journal of Life Science and Pharma Research, 2022)
Post traumatic stiffness and pain are the two main complications which occur after any severe trauma to the knee. Fascia and muscular structures are the major causes for developing stiffness but they are ignored by many physiotherapists as they only focus on intra-articular causes of stiffness. Therefore less research work is available on the effect of myofascial release (MFR) on post-traumatic knee stiffness. Myofascial release can provide immediate effects on stiffness which can be more beneficial if given with conventional protocol of physiotherapy. So it is necessary to study the effect of myofascial release with conventional therapy. To study the effect of myofascial release as an adjunct with conventional therapy on range of motion and pain in post traumatic knee stiffness, 24 subjects of post traumatic knee stiffness both males and females were selected. Their consent was taken and they were given conventional physiotherapy treatment with myofascial release technique. Results were obtained by pre test and post test assessment of visual analogue scale (VAS) and range of motion analysis. According to the statistical analysis of pre test and post test assessment it was found that myofascial release technique significantly improves the range of motion and reduces the pain of affected knee joints. MFR is effective in improving the range of motion and decreasing the pain of affected knee joints in case of posttraumatic knee stiffness when given with conventional physiotherapy protocol.